Electrode and secondary battery including the same

By adding the combination of secondary particles connected by graphene sheets and single-wall carbon nanotube structures to the electrode active material layer of the lithium secondary battery, the problem of conductivity damage is solved, and the battery life is extended and efficiency is improved.

CN119297283APending Publication Date: 2025-01-10LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411340158.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-10-04
Filing Date
2020-09-28
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The conductivity of existing lithium secondary batteries is easily damaged during charging and discharging, resulting in blockage of the conductive network of the electrode active material layer and reducing battery life characteristics and efficiency.

Method used

The carbon nanotube structures that include secondary particles formed by the graphene sheet connection and 2 to 5,000 single-wall carbon nanotube units are used as the conductive agent, and the long-term content is added in an amount of 0.01% to 0.5% in the electrode active material layer. the conductive network to maintain conductivity.

Benefits of technology

It effectively reduces the resistance of the electrode, extends the life characteristics of the battery, and maintains conductivity during repeated charging and discharging, improving the input/output characteristics and life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297283A_ABST
    Figure CN119297283A_ABST
Patent Text Reader

Abstract

The present invention relates to an electrode including an electrode active material layer and a secondary battery including the same, in which the electrode active material layer includes an electrode active material and a conductive agent, and in which the conductive agent includes a first conductive agent and a second conductive agent, wherein the first conductive agent includes secondary particles in a chain form in which a plurality of graphene sheets are arranged in different directions and a portion of one graphene sheet is connected to a portion of another adjacent graphene sheet, and the second conductive agent includes a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded to each other.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an application with an application date of September 28, 2020, application number 202080026379.7, and invention name “Electrode and secondary battery comprising the electrode” (PCT / KR2020 / 013285, date of entry into the national phase on September 29, 2021).

[0002] CROSS-REFERENCE TO RELATED APPLICATIONS

[0003] This application claims the benefit of Korean Patent Application No. 10-2019-0122964, filed on October 4, 2019, the disclosure of which is incorporated herein by reference. Technical Field

[0004] The present invention relates to an electrode including an electrode active material layer and a secondary battery including the electrode, wherein the electrode active material layer includes an electrode active material and a conductive agent, wherein the conductive agent includes a first conductive agent and a second conductive agent, wherein the first conductive agent includes secondary particles in which a plurality of graphene sheets are arranged in different directions and a portion of one graphene sheet is connected to a portion of another adjacent graphene sheet, and the second conductive agent includes a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded to each other, and the carbon nanotube structure is included in the electrode active material layer in an amount of 0.01 wt % to 0.5 wt %. Background Art

[0005] With the recent technological development and increased demand for mobile devices, the demand for batteries as energy sources has increased significantly, and various studies on batteries that can meet various needs have been carried out accordingly. In particular, as a power source for such devices, lithium secondary batteries with excellent life characteristics and cycle characteristics and high energy density have been actively studied.

[0006] A lithium secondary battery refers to a battery that includes a non-aqueous electrolyte containing lithium ions in an electrode assembly, the electrode assembly comprising: a positive electrode including a positive electrode active material capable of inserting / deinserting lithium ions, a negative electrode including a negative electrode active material capable of inserting / deinserting lithium ions, and a microporous separator disposed between the positive electrode and the negative electrode.

[0007] Since the conductivity of the electrode cannot be ensured only by the electrode active material, the resistance of the battery may be too high, and therefore, the electrode generally further includes a conductive agent. Generally, a point-type conductive agent such as carbon black is mainly used, and a linear conductive agent such as carbon nanotubes and carbon nanofibers has also been used to increase the battery capacity by further improving the conductivity.

[0008] Single-walled carbon nanotubes are one of the linear conductive agents, and because of their thin and elongated shape, the conductivity in the electrode active material layer is improved. Therefore, generally, a dispersion including single-walled carbon nanotube units is prepared, wherein the single-walled carbon nanotube units are completely dispersed so that the single-walled carbon nanotube units exist in a single-chain form, and then the dispersion is used to prepare an electrode slurry, and the electrode slurry is used to prepare an electrode active material layer. Therefore, the single-walled carbon nanotube exists in the electrode active material layer as a unit (single chain). However, when the battery is repeatedly charged and discharged, the surface of the single-walled carbon nanotube unit is damaged or the single-walled carbon nanotube unit is damaged, and therefore, it may be difficult to maintain a conductive network in the electrode active material layer. Therefore, the conductive network is blocked or reduced, and this reduces the life characteristics of the battery.

[0009] Therefore, there is also a method of using multi-walled carbon nanotubes, which can ensure conductivity even when the surface of the carbon nanotubes is damaged. However, in the case of multi-walled carbon nanotubes, since they are cut into too short a length due to the structure formed by the growth of nodes as units during the preparation of the dispersion, the improvement of the conductivity of the electrode is limited.

[0010] For planar conductive agents such as graphene, even if the conductivity is excellent, it is difficult to prepare a thin single layer of graphene, and in the case of using thick graphene, the battery efficiency is reduced. In addition, for planar conductive agents, the mobility of the electrolyte in the battery is limited due to the wide planar contact. In addition, since graphene mainly exists in the form of covering the surface of the electrode active material, it is not suitable for forming a long conductive network between the electrode active materials.

[0011] Therefore, a method is needed to reduce the resistance of the electrode and improve the life characteristics of the battery by introducing a new conductive agent. Summary of the invention

[0012] Technical issues

[0013] One aspect of the present invention provides an electrode having low resistance and capable of improving lifespan characteristics of a battery.

[0014] Another aspect of the present invention provides a secondary battery including the electrode.

[0015] Technical Solution

[0016] According to one aspect of the present invention, there is provided an electrode including an electrode active material layer, wherein the electrode active material layer includes an electrode active material and a conductive agent, wherein the conductive agent includes a first conductive agent and a second conductive agent, wherein the first conductive agent includes secondary particles in which a plurality of graphene sheets are arranged in different directions and a portion of one graphene sheet is connected to a portion of another adjacent graphene sheet, the second conductive agent includes a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded to each other, and the carbon nanotube structure is included in the electrode active material layer in an amount of 0.01 wt % to 0.5 wt %.

[0017] According to another aspect of the present invention, a secondary battery including the electrode is provided.

[0018] Beneficial Effects

[0019] Since the electrode according to the present invention includes a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded to each other, a conductive network can be smoothly maintained even during the charge / discharge process of the battery. Therefore, the resistance of the electrode can be maintained at a low level, and the life characteristics of the battery can be improved. In addition, since the carbon nanotube structure is present in the electrode in the form of a long rope, even if the battery is continuously charged and discharged, the decrease in conductivity caused by damage to the carbon nanotube structure can be suppressed, and a long conductive network can be formed. In addition, since the electrode includes a secondary particle in which a portion of one graphene sheet is connected to a portion of another adjacent graphene sheet, the resistance of the battery can be further reduced due to the excellent conductivity of the secondary particles. In addition, since the secondary particles are mainly arranged on the surface of the electrode active material and help to form a short conductive network, the conductive network can be uniformly formed on the entire electrode due to the combined use of the secondary particles and the carbon nanotube structure. In addition, due to the presence of the secondary particles, at least a portion of the carbon nanotube structure is fixed to the electrode active material by covering at least a portion of the carbon nanotube structure, so that the conductive network can be maintained even during repeated charging and discharging of the battery. In addition, since the secondary particles can be used as a hub to suppress the localization of electrons due to the attraction of electrons to the carbon nanotube structure in the electrode active material layer, the conductivity of the electrode active material layer can be improved, thereby further improving the battery life. In addition, since the orientation of the carbon nanotube structure can be more diversified by the graphene sheets existing in various orientations in the secondary particles, the conductive network can be evenly distributed in the electrode active material layer. In addition, since the graphene sheets in the secondary particles have a shorter lateral dimension than conventional graphene, the inhibition of the mobility of the electrolyte solution can be minimized. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1These are scanning electron microscope (SEM) images of the multi-walled carbon nanotube unit (A) used in the comparative example of the present invention and the carbon nanotube structure (B, C) used in the examples.

[0021] Figure 2 These are transmission electron microscope (TEM) images of the carbon nanotube structure (A) used in the example of the present invention and the single-walled carbon nanotube unit (B) used in the comparative example.

[0022] Figure 3 Schematic diagram showing a process of forming a graphene sheet included in secondary particles used in Examples of the present invention.

[0023] Figure 4 TEM images of the secondary particles (a) used in Preparation Example 1 and the secondary particles (b) used in Preparation Example 2 of the present invention.

[0024] Figure 5 are SEM images and TEM images of the secondary particles used in Examples of the present invention.

[0025] Figure 6 This is a SEM image of the electrode of Example 1 of the present invention.

[0026] Figure 7 This is a SEM image of the electrode of Example 1 of the present invention.

[0027] Figure 8 This is a SEM image of the electrode of Example 1 of the present invention.

[0028] Fig. 9 This is a SEM image of the electrode of Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0029] It will be understood that the words or terms used in the specification and claims should not be interpreted as the meanings defined in commonly used dictionaries, and it will be further understood that, based on the principle that the inventor can appropriately define the meanings of words or terms to best interpret the present invention, these words or terms should be interpreted as having meanings consistent with the technical concept of the present invention and the meanings in the context of related technologies.

[0030] The terms used in this specification are only used to describe exemplary embodiments and are not intended to limit the present invention. Unless otherwise indicated, terms in the singular form may include plural forms.

[0031] It will be further understood that the terms “comprises,” “comprising,” or “having” in this specification specify the presence of stated features, numbers, steps, elements, or a combination thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, elements, or a combination thereof.

[0032] In the present specification, unless otherwise specifically stated, the expression "%" means % by weight.

[0033] In the present specification, the expression "specific surface area" is measured by the BET method, wherein, specifically, the specific surface area can be calculated from the nitrogen adsorption amount at liquid nitrogen temperature (77K) using BELSORP-mini II manufactured by Bell Japan.

[0034] The “average particle size (D 50 The average particle size D can be defined as the particle size at which the cumulative volume in the particle size distribution curve is 50%. For example, the average particle size D can be measured by using a laser diffraction method. 50 Laser diffraction can usually measure particle sizes from submicron to several millimeters, and can obtain results with high repeatability and high resolution.

[0035] In the present invention, the expression "single-walled carbon nanotube unit" means a tubular unit having a single wall composed of carbon atoms, and the expression "multi-walled carbon nanotube unit" means a tubular unit having multiple walls composed of carbon atoms.

[0036] The expression "graphene" in this specification means a carbonaceous structure having a form of stacking a single graphite plane or a plurality of graphite planes, having flexibility, and having a thin film form.

[0037] Hereinafter, the present invention will be described in detail.

[0038] electrode

[0039] An electrode according to the present invention includes an electrode active material layer, wherein the electrode active material layer includes an electrode active material and a conductive agent, wherein the conductive agent includes a first conductive agent and a second conductive agent, wherein the first conductive agent includes secondary particles in which a plurality of graphene sheets are arranged in different directions and a portion of one graphene sheet is connected to a portion of another adjacent graphene sheet, the second conductive agent includes a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded to each other, and the carbon nanotube structure is included in the electrode active material layer in an amount of 0.01 wt % to 0.5 wt %.

[0040] The electrode may include an electrode active material layer. The electrode may further include a current collector, and in this case, the electrode active material layer may be provided on one surface or both surfaces of the current collector.

[0041] The current collector is not particularly limited as long as it has conductivity and does not cause adverse chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, their alloys, these materials surface-treated with one of carbon, nickel, titanium, silver, etc., or calcined carbon can be used.

[0042] The current collector generally can have a thickness of 3 μm to 500 μm, and fine irregularities can be formed on the surface of the current collector to improve the adhesion of the electrode active material. In addition, the electrode current collector can be used in various shapes such as films, sheets, foils, meshes, porous bodies, foams, non-woven fabric bodies, etc.

[0043] The electrode active material layer can include an electrode active material and a conductive agent.

[0044] The electrode active material can be a positive electrode active material or a negative electrode active material commonly used in the art, but its type is not particularly limited.

[0045] For example, as the positive electrode active material, lithium oxides containing lithium and at least one metal such as cobalt, manganese, nickel, or aluminum can be used. Specifically, the lithium oxides can include: lithium manganese-based oxides (such as LiMnO2, LiMn2O, etc.); lithium cobalt-based oxides (such as LiCoO2, etc.); lithium nickel-based oxides (such as LiNiO2, etc.); lithium nickel manganese-based oxides (such as LiNi 1- Y1 Mn Y1 O2 (where 0 < Y1 < 1), LiMn 2-Z1 Ni z1 O4 (where 0 < Z1 < 2), etc.); lithium nickel cobalt-based oxides (such as LiNi 1- Y2 Co Y2 O2 (where 0 < Y2 < 1)); lithium manganese cobalt-based oxides (such as LiCo 1-Y3 Mn Y3 O2 (where 0 < Y3 < 1), LiMn 2-Z2 Co z2 O4 (where 0 < Z2 < 2), etc.); lithium nickel cobalt manganese-based oxides (such as Li(Ni P1 Co Q1 Mn R1 )O2 (where 0 < P1 < 1, 0 < Q1 < 1, 0 < R1 < 1, and P1 + Q1 + R1 = 1) or Li(Ni P2 Co Q2 Mn R2 )O4 (where 0 < P2 < 2, 0 < Q2 < 2, 0 < R2 < 2, and P2 + Q2 + R2 = 2), etc.); or lithium nickel cobalt manganese-transition metal (M) oxides (such as Li(Ni P3 CoQ3 Mn R3 M 1 S )O2 (where M 1 is selected from the group consisting of aluminum (Al), copper (Cu), iron (Fe), vanadium (V), chromium (Cr), titanium (Ti), zirconium (Zr), zinc (Zn), tantalum (Ta), niobium (Nb), magnesium (Mg), boron (B), tungsten (W), and molybdenum (Mo), and P3, Q3, R3, and S are atomic fractions of each independent element, where 0 < P3 < 1, 0 < Q3 < 1, 0 < R3 < 1, 0 < S < 1, and P3 + Q3 + R3 + S = 1), etc.), and may include any one of them or a mixture of two or more of them.

[0046] The negative electrode active material may include, for example: carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metal compounds alloyable with lithium such as silicon (Si), aluminum (Al), tin (Sn), lead (Pb), zinc (Zn), bismuth (Bi), indium (In), magnesium (Mg), gallium (Ga), cadmium (Cd), Si alloy, Sn alloy, or Al alloy; metal oxides that may or may not be doped with lithium such as SiO v (0 < v < 2), SnO2, vanadium oxides, and lithium vanadium oxides; or composites including metal compounds and carbonaceous materials such as Si-C composites or Sn-C composites, and any one of them or a mixture of two or more of them may be used. In addition, a thin film of metallic lithium may be used as the negative electrode active material. In addition, both low-crystalline carbon and high-crystalline carbon may be used as the carbonaceous materials.

[0047] The electrode active material may be included in an amount of 70 wt% to 99.5 wt%, for example 80 wt% to 99 wt%, based on the total weight of the electrode active material layer. When the amount of the electrode active material satisfies the above range, excellent energy density, electrode adhesion, and conductivity can be achieved.

[0048] The conductive agent may include a first conductive agent and a second conductive agent.

[0049] The first conductive agent may include secondary particles, and the second conductive agent may include a carbon nanotube structure.

[0050] (1) Secondary particles

[0051] The first conductive agent may include secondary particles, and preferably, the first conductive agent may be secondary particles. The secondary particles may include a structure in which a plurality of graphene sheets are connected. Specifically, in the secondary particles, at least two graphene sheets may be directly connected to each other or may be indirectly connected. More specifically, the secondary particles have a form in which a part of one graphene sheet is connected to a part of an adjacent another graphene sheet.

[0052] A plurality of graphene sheets may be connected to each other to form a chain-shaped secondary particle, and more specifically, the chain-shaped secondary particle may partially include an aggregation region of a plurality of graphene sheets. Since the secondary particles have a unique chain-shaped direct connection structure, the electrical conductivity and thermal conductivity of the conductive agent including the secondary particles may be excellent.

[0053] When described in more detail, typical planar graphene has a two-dimensional arrangement due to the small thickness compared to the width of the plane. Therefore, most of the conductive networks formed in the electrode are formed based on the two-dimensional arrangement. In contrast, the graphene sheets included in the secondary particles include a plurality of graphene sheets with random arrangement. Specifically, the secondary particles include a plurality of graphene sheets arranged in different directions (directions perpendicular to the plane of the graphene sheets). That is, the secondary particles can be in the form of a three-dimensional arrangement, which is formed by connecting the graphene sheets arranged in various directions to each other, and more specifically, since the graphene sheets are in the form of chains, i.e., arranged longitudinally to have a predetermined length while having a three-dimensional arrangement, the conductive network formed in the electrode can be formed based on the three-dimensional arrangement. Therefore, since a conductive network in each direction can be formed, and a conductive connection between a linear carbon nanotube structure and the secondary particles can be effectively formed, the conductivity of the electrode can be significantly improved. In this article, the graphene sheets may also include a plurality of graphene sheets arranged in the same direction, but, in this case, the graphene sheets also include a plurality of graphene sheets arranged in different directions.

[0054] The secondary particles may further include a connecting portion connected to at least a portion of the graphene sheets in the plurality of graphene sheets. In the present invention, during the preparation of the secondary particles, the primary particles such as carbon black are broken by a continuous oxidation reaction to form graphene sheets, and there may also be a portion that maintains its original shape without being broken. In this case, the portion that maintains its shape may correspond to the connecting portion. Therefore, the connecting portion may have a non-graphene shape, and the expression "non-graphene shape" different from the above-mentioned graphene sheet may mean a block having a thickness greater than the graphene sheet, and more specifically may be a block that is not completely broken.

[0055] A portion of each of the plurality of graphene sheets may be directly connected to each other. Alternatively, at least a portion of the plurality of graphene sheets may be connected to each other through a connecting portion, and specifically, at least a portion of each of the plurality of graphene sheets may be connected to the connecting portion. The secondary particles of the present invention may include these two connection methods.

[0056] Secondary particles are formed by modifying carbon black in the form of nearly spherical particles, such as acetylene black, furnace black, thermal black, channel black and lamp black, by oxidation treatment. Figure 3 Schematic diagram of the present invention, the structure of carbon black can be changed by oxidation treatment to form particles including a plurality of graphene sheets. In the case where the carbon black is in the form of secondary particles, secondary particles in which particles including a plurality of graphene sheets are aggregated can be formed.

[0057] The average thickness of the graphene sheet may be 10 nm or less, particularly 0.34 nm to 10 nm, and more particularly 0.34 nm to 5 nm. In the case where the average thickness of the graphene sheet satisfies the above range, since the flexibility peculiar to the graphene sheet can be exhibited, the surface contact due to the graphene sheet is improved, and therefore, the conductivity of the conductive agent may be excellent. The graphene sheet may have a shape in which 30 or less graphene layers are stacked. The average thickness of the graphene sheet may correspond to an average value of the thickness of 100 graphene sheets measured by identifying the electrode through a transmission electron microscope (TEM).

[0058] The lateral size of the graphene sheet may be 10 nm to 500 nm, in particular 10 nm to 300 nm or less, and more particularly 10 nm to 200 nm, for example 50 nm to 100 nm. The lateral size of the graphene sheet may be regulated according to the degree of heat treatment, for example, the lateral size of the graphene sheet may be regulated by further performing an additional heat treatment in an inert atmosphere after the oxidation treatment. When the lateral size of the graphene sheet satisfies the above range, the ions in the electrolyte may be smoothly diffused in the electrode. Therefore, the fast charging characteristics of the battery may be improved, and the rate performance may also be improved. The lateral size of the graphene sheet represents the average value of the lateral sizes of 100 graphene sheets observed by a scanning electron microscope (SEM) or TEM, and in this article, the expression "lateral size" represents the longest length when it is assumed that there is a line from one point to another in a graphene sheet.

[0059] Based on the total weight of the secondary particles, the oxygen content of the secondary particles may be 1 wt% or more, for example, 1 wt% to 10 wt%. When the oxygen content of the secondary particles satisfies the above range, since the secondary particles can be smoothly dispersed in the electrode slurry formed during the preparation of the electrode, the conductivity of the electrode can be improved and the capacity of the prepared battery can be increased. The oxygen content can be measured by elemental analysis of carbon (C), hydrogen (H), oxygen (O) and nitrogen (N).

[0060] The oxygen content can be achieved during the oxidation treatment of the carbon black. Specifically, oxygen-containing functional groups can be formed on the surface of the secondary particles by the oxidation treatment. The oxygen-containing functional groups can be at least one selected from the group consisting of carboxyl, hydroxyl and carbonyl. After the oxidation treatment, the oxygen content can be further regulated by performing a heat treatment on the secondary particles in an inert atmosphere.

[0061] The secondary particles may have a higher degree of graphitization than the carbon black before the oxidation treatment. Specifically, because the high structural stress caused by the surface tension of the spherical carbon black may be partially eliminated due to the formation of planar graphene sheets, and the structural defects caused by the curvature may be minimized to form a stable sp 2 structure, thus the graphitization degree of the prepared conductive agent can be increased.

[0062] During Raman spectroscopy measurement, the D / G peak ratio of the secondary particles may be 2.0 or less, specifically 0.9 to 2.0, and more specifically 1.1 to 1.8. In the Raman spectrum, at 1590 cm -1 The G peak nearby is due to the sp 2 Key E 2g vibration mode, and when the sp 2 When the bond is defective, it appears at 1350cm -1 That is, when the D / G peak ratio is satisfied, it indicates that a high degree of graphitization can be obtained. Therefore, when the secondary particles are used, the capacity and electrical characteristics of the battery can be improved due to the high conductivity of the secondary particles.

[0063] The secondary particle may have a value calculated by the following Equation 1 of 0.2 or less, specifically 0 to 0.20, and more specifically 0 to 0.15, for example 0 to 0.1.

[0064] [Equation 1]

[0065]

[0066] In Equation 1, a is the specific surface area (m 2 / g), b is the iodine adsorption value (mg / g) of the secondary particles. In the case where the secondary particles include a pore structure inside or between the particles, small-sized nitrogen (N2) molecules can be adsorbed in the pores in large quantities. In contrast, since iodine (I2) is a relatively large molecule, it is difficult to enter the pores compared to nitrogen, so the iodine adsorption value is not large. That is, when there is a pore structure, the value according to equation 1 increases. In other words, in the secondary particles, the value of 0.2 or less according to equation 1 means that the secondary particles do not include micropores or include a small amount of micropores. That is, in the absence of micropores, since the adsorption degree of iodine is similar to that of nitrogen, the value of equation 1 decreases. This means that the surface of the secondary particles is a free surface. Specifically, most carbon black is modified into a hollow structure by oxidation treatment, and the structure is broken by continuous oxidation treatment to form a graphene sheet. In this case, the graphene sheet can be formed to open outward without forming a pore structure.

[0067] The specific surface area (m 2 / g) is 200m 2 / g or higher, especially 200m 2 / g to 1100m 2 / g, more particularly 300m 2 / g to 1100m 2 / g, for example 500m 2 / g to 900m 2 When the above specific surface area range is satisfied, this means that the area of ​​the graphene sheet in the secondary particles is large, and thus the conductivity of the electrode can be ensured even if the amount of the secondary particles in the electrode is small.

[0068] The secondary particles may be included in the electrode active material layer in an amount of 0.01 wt % to 1.0 wt %, particularly 0.05 wt % to 0.5 wt %, and more particularly 0.1 wt % to 0.5 wt %. In the case where the amount of the secondary particles satisfies the above range, the adhesion and conductivity of the electrode can be significantly improved by using only a small amount of the secondary particles, and the input / output characteristics and life characteristics of the battery can be improved.

[0069] Since the secondary particles are prepared by oxidizing carbon black composed of multiple primary particles, the secondary particles have a unique shape including multiple graphene sheets generated by the rupture of spherical primary particles. Therefore, the secondary particles have both carbon black and graphene properties to some extent, and the secondary particles can have abundant surface oxygen functional groups during the oxidation process. Therefore, due to the characteristics of carbon black, the secondary particles can solve the problems of low exfoliation and poor dispersibility of conventional graphene, and can maintain the high conductivity of thin graphene sheets. In addition, when the secondary particles are used together with the carbon nanotube structure, since the mutual aggregation phenomenon (aggregation of carbon nanotube structure and secondary particles) caused by π-π stacking (π-πstacking) caused by the homogeneous sp2 surface structure of carbon can be suppressed by the abundant surface oxygen functional groups of the secondary particles, the conductive network in the electrode can be formed more tightly by contributing to the dispersibility of the carbon nanotube structure.

[0070] (2) Carbon nanotube structure

[0071] The second conductive agent may include a carbon nanotube structure, and preferably, the second conductive agent may be a carbon nanotube structure.

[0072] The carbon nanotube structure may include a plurality of single-walled carbon nanotube units. Specifically, the carbon nanotube structure may be a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded to each other. More specifically, in consideration of the durability and conductive network of the electrode, the carbon nanotube structure is most preferably a carbon nanotube structure in which 2 to 4,500, preferably 50 to 4,000, and more preferably 1,000 to 4,000 single-walled carbon nanotube units are bonded to each other.

[0073] The single-walled carbon nanotube units can be arranged side by side and combined in a carbon nanotube structure (having a flexible cylindrical structure in which the units are combined so that the long axes of the units are parallel to each other) to form a carbon nanotube structure. The carbon nanotube structure is connected to each other in the electrode to form a network structure.

[0074] Conventional electrodes including carbon nanotubes are usually prepared in the following manner: a conductive agent dispersion is prepared by dispersing bundle type or entangled type carbon nanotubes (in the form of single-walled carbon nanotube units or multi-walled carbon nanotube units attached or entangled to each other) in a dispersion medium, and then using the conductive agent dispersion. In this case, since the carbon nanotubes are completely dispersed in the conventional conductive agent dispersion, the carbon nanotubes exist as a conductive agent dispersion in which single-chain carbon nanotube units are dispersed. With respect to conventional conductive agent dispersions, since the carbon nanotube units are easily cut by excessive dispersion processes, the length of the carbon nanotube units is shorter than the initial length. In addition, the carbon nanotube units may also be easily cut during the rolling process of the electrode, and due to excessive changes in the volume of the electrode active material during battery operation, the carbon nanotube units (particularly single-walled carbon nanotube units) may be additionally cut or the surface is damaged. Therefore, due to the reduced conductivity of the electrode, the input / output characteristics and life characteristics of the battery are deteriorated. In addition, regarding the multi-walled carbon nanotube units, the structural defects are high due to the node growth mechanism (these units are not smooth and linear, but have nodes due to defects generated during the growth process). Therefore, the multi-walled carbon nanotube units are more easily cut during the dispersion process (see Figure 1 A), and the short-cut multi-walled carbon nanotube units can be easily aggregated by π-π stacking caused by the carbon surface bonding structure (sp2) of the unit. Therefore, it is more difficult to make the multi-walled carbon nanotube units more uniformly dispersed in the electrode slurry.

[0075] Alternatively, regarding the carbon nanotube structure included in the electrode of the present invention, since the carbon nanotube structure is a structure in which 2 to 5,000 single-walled carbon nanotube units maintaining relatively high crystallinity without structural defects are arranged side by side and bonded together (see Figure 1 B and C and Figure 2A) in the form of a rope, even if the volume of the electrode active material changes, the single-walled carbon nanotube unit will not be cut, and its length can be maintained smoothly, so that the conductivity of the electrode can be maintained even during the continuous charge / discharge process of the battery. In addition, since the high conductivity of the single-walled carbon nanotube unit with high crystallinity leads to an increase in the conductivity of the electrode, the input / output characteristics and life characteristics of the battery can be significantly improved. In addition, since the carbon nanotube structure is interconnected in the electrode and has a network structure, the excessive change in the volume of the electrode active material can be suppressed, thereby preventing the generation of cracks, and a strong conductive network can be ensured at the same time. In addition, even if cracks are generated in the electrode active material, the conductive network can be maintained because the carbon nanotube structure can connect the electrode active material while passing through the cracks. In addition, since the carbon nanotube structure is not easily damaged and can maintain its long shape, the conductive network can be enhanced over the entire electrode active material layer. In addition, by suppressing the peeling of the electrode active material, the electrode adhesion can be significantly improved.

[0076] In particular, from the perspective of using in combination with secondary particles, the secondary particles are mainly arranged on the surface of the electrode active material to help ensure conductivity on a small length scale, but through the network structure and its larger length, the carbon nanotube structure can also help ensure conductivity on a large length scale. In addition, since the secondary particles are present when covering at least a portion of the carbon nanotube structure, the conductive network can be tightly maintained even if the battery is repeatedly charged and discharged. Therefore, if the secondary particles are used in combination with the carbon nanotube structure, since a tight and uniform conductive network can be formed on the entire electrode active material layer while reducing the total amount of the conductive agent used, the input / output characteristics and life characteristics of the battery can be significantly improved.

[0077] In the carbon nanotube structure, the average diameter of the single-walled carbon nanotube unit can be 0.5nm to 5nm, for example, 1nm to 5nm. When this average diameter is met, the conductivity of the electrode can reach the maximum even with a very small amount of conductive agent. When the prepared electrode is observed by TEM, the average diameter corresponds to the average value of the diameters of the first 100 single-walled carbon nanotube units with larger diameters and the last 100 single-walled carbon nanotube units with smaller diameters.

[0078] In the carbon nanotube structure, the average length of the single-walled carbon nanotube unit can be 1 μm to 100 μm, for example, 5 μm to 50 μm. When this average length is met, since a long conductive path for conductive connection between electrode active materials can be formed and a unique network structure can be formed, the conductivity of the electrode can be maximized even with a very small amount of conductive agent. When the prepared electrode is observed by TEM, the average length corresponds to the average of the lengths of the first 100 single-walled carbon nanotube units with longer lengths and the last 100 single-walled carbon nanotube units with shorter lengths.

[0079] The specific surface area of ​​a single-walled carbon nanotube unit can be 500m 2 / g to 1,000m 2 / g, for example 600m 2 / g to 800m 2 / g. When the specific surface area satisfies the above range, since the conductive path in the electrode can be smoothly ensured by the wide specific surface area, the conductivity of the electrode can be maximized even with a very small amount of conductive agent. The specific surface area of ​​the single-walled carbon nanotube unit can be specifically calculated by the nitrogen adsorption at liquid nitrogen temperature (77K) using Bell Japan's BELSORP-mini II.

[0080] The average diameter of the carbon nanotube structure can be 2nm to 200nm, particularly 5nm to 150nm, and more particularly 50nm to 120nm. When the average diameter meets the above range, since it effectively forms a conductive network structure and is conducive to connecting active materials, excellent conductivity can be achieved. When the prepared electrode is observed by SEM, the average diameter corresponds to the average value of the diameters of the first 100 carbon nanotube structures with larger diameters and the last 100 carbon nanotube structures with smaller diameters.

[0081] The average length of the carbon nanotube structure can be 1 μm to 500 μm, particularly 5 μm to 100 μm, and more particularly 10 μm to 70 μm. When the average length meets the above range, since it effectively forms a conductive network structure and is conducive to connecting electrode active materials, excellent conductivity can be achieved. When the prepared electrode is observed by SEM, the average length corresponds to the average value of the lengths of the first 100 carbon nanotube structures with longer lengths and the last 100 carbon nanotube structures with shorter lengths.

[0082] The carbon nanotube structure can be included in the electrode active material layer in an amount of 0.01 wt % to 0.5 wt %, can be specifically included in an amount of 0.01 wt % to 0.15 wt %, and can be more specifically included in an amount of 0.01 wt % to 0.1 wt %. When the amount of the carbon nanotube structure meets the above range, since the conductive path in the electrode can be ensured, the life characteristics of the battery can be improved while the electrode resistance is kept at a low level. When preparing a conductive agent dispersion, the carbon nanotubes are fully dispersed (as a conventional dispersion method, in which the carbon nanotubes are dispersed so that the single-chain carbon nanotube units are separated from each other as much as possible), the carbon nanotube structure will not be generated, or even if the carbon nanotube structure is inadvertently generated, only a very small amount (e.g., 0.0005 wt %) of the carbon nanotube structure will be generated. That is, the above-mentioned amount range may never be reached in the usual way. Since the carbon nanotube structure is in a form in which 2 to 5,000 single-walled carbon nanotube units are arranged side by side and combined, even if the volume of the electrode active material changes, the carbon nanotube structure will not be cut and its length can be smoothly maintained. Therefore, due to the high conductivity of the carbon nanotube structure, the conductivity of the electrode can be maintained and the conductivity of the electrode can be smoothly ensured. Therefore, even if the amount of the carbon nanotube structure in the electrode is small, the input / output characteristics and life characteristics of the battery can be excellent.

[0083] In some cases, the single-walled carbon nanotube units can be surface treated by oxidation or nitridation to improve affinity with the dispersion.

[0084] The weight ratio of the secondary particles to the carbon nanotube structure may be in the range of 100:1 to 100:200, particularly 100:2 to 100:100, and more particularly 100:5 to 100:50. When the weight ratio satisfies the above range, the total amount of the conductive agent for an appropriate level of conductivity can be reduced while increasing the solid content of the electrode slurry. In addition, since the adhesion and conductivity of the electrode can be improved at the same time, the input / output characteristics and life characteristics of the battery can be significantly improved.

[0085] The electrode active material layer may further include a binder. The binder is used to ensure the adhesion between the electrode active materials and the adhesion of the electrode active material to the current collector, wherein the common binder used in the art can be used, and there is no particular restriction on its type. The binder may include, for example: polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, carboxymethyl cellulose (carboxymethyl cellulose: CMC), styrene-butadiene rubber (SBR), fluororubber or various copolymers thereof, and any one of them or a mixture of more than two thereof may be used.

[0086] The binder may be included in an amount of 10 wt % or less, for example 0.1 wt % to 5 wt % based on the total weight of the electrode active material layer. When the amount of the binder satisfies the above range, excellent electrode adhesion may be achieved while minimizing the increase in electrode resistance.

[0087] The electrode active material layer may further include at least one of polyvinylidene fluoride and hydrogenated nitrile rubber. Polyvinylidene fluoride and hydrogenated nitrile rubber play a role in helping to disperse bundle-type or entangled single-walled carbon nanotubes or bundle-type or entangled multi-walled carbon nanotubes in the conductive agent dispersion used in electrode preparation, and because the electrode slurry is prepared from the conductive agent dispersion, polyvinylidene fluoride and hydrogenated nitrile rubber may be included in the electrode.

[0088] Method for preparing electrode

[0089] Next, a method for producing the electrode of the present invention will be described.

[0090] The method for preparing an electrode of the present invention may include the following steps: preparing a secondary particle dispersion and a carbon nanotube structure dispersion (S1); and forming an electrode slurry including the secondary particle dispersion, the carbon nanotube structure dispersion and an electrode active material (S2).

[0091] (1) Preparation of Secondary Particle Dispersion and Carbon Nanotube Structure Dispersion (S1)

[0092] 1) Preparation of secondary particle dispersion

[0093] The preparation of a secondary particle dispersion includes: preparing primary particles; modifying the primary particles by oxidation treatment, wherein the step of modifying the primary particles by oxidation treatment includes at least one of the following: a) performing a first heat treatment on the primary particles at a temperature of 200°C to 800°C under an oxygen atmosphere or an air atmosphere; and b) reacting the primary particles with acidic vapor at 120°C to 300°C.

[0094] In preparing the primary particles, the primary particles may be carbon black. Specifically, the primary particles may include at least one selected from the group consisting of acetylene black, furnace black, thermal black, channel black, and lamp black. More specifically, the primary particles may be acetylene black produced at the highest temperature to substantially have an excellent degree of graphitization.

[0095] The preparation of primary particles may include pyrolysis of acetylene gas, and carbon black, such as acetylene black, may be formed by pyrolysis. The acetylene gas may be high purity acetylene gas, and specifically may be acetylene gas with a purity of 95% or more, such as 98% or more.

[0096] The pyrolysis of acetylene gas may be performed at a temperature of 1500° C. or higher, particularly 1500° C. to 2200° C., and more particularly 1500° C. to 2000° C. In the case where the temperature satisfies the above range, the degree of graphitization of the primary particles prepared will be high, and the degree of graphitization of the secondary particles prepared therefrom will also be high. Therefore, the conductivity of the conductive agent can be improved.

[0097] The primary particles may be carbon black, but acetylene black may be preferred in terms of the following aspects. The graphene sheets included in the secondary particles of the present invention may be formed by modifying the surface of the primary particles by oxidation treatment. The surface of the acetylene black formed by pyrolysis may have a high degree of graphitization. Therefore, when acetylene black is subjected to oxidation treatment, the structure of the graphene sheets may be smoothly formed, compared to the case where other carbon blacks that inevitably contain some oxygen functional groups on their surfaces are subjected to oxidation treatment.

[0098] Pyrolysis can be performed in such a manner that after the internal temperature of the reaction furnace is adjusted to the above temperature range, acetylene gas is introduced into the reaction furnace and pyrolysis is immediately performed. In addition, in this process, air, oxygen and H2O can be further added to regulate the density of the conductive agent and the oxygen functional group, and the connection structure in the secondary particles can be regulated.

[0099] Modification of the primary particles by oxidation treatment may include at least one of the following: a) performing a first heat treatment on the primary particles at a temperature of 200°C to 800°C under an oxygen atmosphere or an air atmosphere (step a); and b) reacting the primary particles with acidic vapor at 120°C to 300°C (step b).

[0100] In step a, an oxygen atmosphere or an air atmosphere may be formed by introducing oxygen or air into a reaction furnace containing primary particles. Specifically, a graphene sheet structure may be formed by an oxidation process in a reaction furnace according to an appropriate flow rate and rate of oxygen or air, a reaction temperature, and a reaction time set during the first heat treatment. In addition, the conditions of the oxidation process may vary according to differences in the density of the primary particles and the amount of oxygen functional groups.

[0101] In step a, the first heat treatment may be performed by regulating the temperature of the reaction furnace in the reaction furnace containing the primary particles. The first heat treatment may be performed at a heat treatment temperature of 200° C. to 800° C., and specifically may be performed at a heat treatment temperature of 200° C. to 450° C. When the heat treatment temperature satisfies the above range, an excessively fast oxidation reaction of the primary particles may be prevented, and a graphene sheet having a desired size may be formed. The first heat treatment may be performed for 1 hour to 50 hours.

[0102] In step b, the primary particles may react with acidic vapor to be oxidized to form graphene sheets. Specifically, the acidic vapor may be vapor derived from an acidic solution such as HCl and HNO3. The temperature of the acidic vapor reacting with the primary particles may be in the range of 120°C to 300°C.

[0103] After the primary particles are modified by oxidation treatment, a second heat treatment process may be further performed in an inert atmosphere to increase the size of the formed graphene sheets. Specifically, the method for preparing secondary particles may further include: after the primary particles are modified by oxidation treatment, performing a second heat treatment on the primary particles modified by oxidation treatment in an inert atmosphere at a temperature of 500°C or higher. In this case, the inert atmosphere may be formed by a vacuum or any one gas selected from the group consisting of helium, argon and nitrogen. The second heat treatment temperature may be 500°C or higher, particularly 500°C to 2800°C, and more particularly 600°C to 1600°C.

[0104] The mechanism of forming secondary particles described in the present invention can be as follows. During the preparation of secondary particles, spherical or chain-type carbon black is subjected to oxidation treatment, wherein the average diameter of the spherical primary particles is 50nm or less, and the primary particles share a structure under specific conditions, such as acetylene black. In this case, the penetration and oxidation reaction of the oxidant (e.g., oxygen and acidic vapor) occur in the defective part, such as the grain boundary (grain boundary) or dislocation (dislocation) present in the unit microstructure of the carbon black. When the oxidation treatment is performed for a predetermined time within the temperature range described in the preparation method, the oxidant penetrates into the internal microstructure of the carbon black, thereby causing an oxidation reaction. In this case, in order to alleviate the structural stress of the microstructure of the primary particles having a larger radius of curvature than the radius of curvature of the surface of the spherical primary particles, an oxidation reaction occurs rapidly in the primary particles. Therefore, the internal carbon atoms are oxidized into gases such as CO, CO2 and CH4, and the primary particles are converted into hollow types. While the surface structure of the hollow primary particles is also destroyed by the continuous oxidation treatment, most of the structural stress remaining in the spherical primary particles is also relieved, and graphene sheets appear in this process. Therefore, as the average diameter of the carbon black as the primary particles decreases, the internal density of the particles decreases, and the amount of oxygen functional groups in the primary particles is greater than the amount of oxygen functional groups on the surface of the primary particles, the modification process can be accelerated. In addition, in terms of the fact that step a can further accelerate the modification process, step a is more desirable than step b.

[0105] After preparing a mixed solution including the secondary particles prepared by the above method, a dispersion medium and a dispersant, a secondary particle dispersion can be prepared by using a homogenizer, a bead mill, a ball mill, a basket mill, a grinder, a universal stirrer, a transparent mixer, a pin mill, a TK mixer or an ultrasonic treatment method. Since the dispersion medium and the dispersant can be the same as the dispersion medium and the dispersant used in the preparation of the carbon nanotube structure dispersion described later, the dispersion medium and the dispersant will be described below.

[0106] 2) Preparation of carbon nanotube structure dispersion

[0107] The preparation of the carbon nanotube structure dispersion may include the following steps: preparing a mixed solution including a dispersion medium, a dispersant, and bundle-type single-walled carbon nanotubes (bonded bodies or aggregates of single-walled carbon nanotube units) (S1-1); and dispersing the bundle-type single-walled carbon nanotubes by applying a shear force to the mixed solution, thereby forming a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded side by side (S1-2).

[0108] In step S1-1, a mixed solution can be prepared by adding bundled single-walled carbon nanotubes and a dispersant to a dispersion medium. The bundled single-walled carbon nanotubes exist in the form of bundles combining the above-mentioned single-walled carbon nanotube units, wherein the bundled carbon nanotubes generally include 2 or more, substantially 500 or more, for example, 5,000 or more single-walled carbon nanotube units.

[0109] The specific surface area of ​​bundled single-walled carbon nanotubes can be 500m 2 / g to 1,000m 2 / g, for example 600m 2 / g to 800m 2 When the specific surface area satisfies the above range, since a conductive path in the electrode can be smoothly ensured by a wide specific surface area, the conductivity of the electrode can be maximized even with a very small amount of the conductive agent.

[0110] The bundled single-walled carbon nanotubes may be included in the mixed solution in an amount of 0.1 wt % to 1.0 wt %, for example, 0.2 wt % to 0.5 wt %. When the amount of the bundled single-walled carbon nanotubes satisfies the above range, since the bundled single-walled carbon nanotubes are dispersed at an appropriate level, a carbon nanotube structure may be formed at an appropriate level, and dispersion stability may be improved.

[0111] The dispersion medium may include, for example: an amide-based polar organic solvent such as dimethylformamide (DMF), diethylformamide, dimethylacetamide (DMAc) and N-methylpyrrolidone (NMP); an alcohol such as methanol, ethanol, 1-propanol, 2-propanol (isopropanol), 1-butanol (n-butanol), 2-methyl-1-propanol (isobutanol), 2-butanol (sec-butanol), 1-methyl-2-propanol (tert-butanol), pentanol, hexanol, heptanol or octanol; a glycol such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propylene glycol, 1,3-butanediol, 1,5-pentanediol or hexanediol. Alcohol; polyhydric alcohol, such as glycerol, trimethylolpropane, pentaerythritol or sorbitol; glycol ether, such as ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, tetraethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, triethylene glycol monoethyl ether, tetraethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether or tetraethylene glycol monobutyl ether; ketone, such as acetone, methyl ethyl ketone, methyl propyl ketone or cyclopentanone; ester, such as ethyl acetate, γ-butyrolactone and ε-propiolactone, and any one of them or a mixture of two or more thereof can be used, but the present invention is not limited thereto. Specifically, the dispersion medium can be N-methylpyrrolidone (NMP).

[0112] The dispersant may include at least one selected from hydrogenated nitrile rubber, polyvinylidene fluoride, and carboxymethyl cellulose, and specifically may be polyvinylidene fluoride or hydrogenated nitrile rubber.

[0113] In the conductive agent dispersion, the weight ratio of the bundle-type carbon nanotubes to the dispersant may be in the range of 1:0.1 to 1:7, for example, 1:1 to 1:6. When the weight ratio satisfies the above range, since the bundle-type single-walled carbon nanotubes are dispersed at an appropriate level, the carbon nanotube structure may be formed at an appropriate level, and the dispersion stability may be improved.

[0114] The solid content in the mixed solution can be in the range of 0.1 wt % to 20 wt %, for example, 1 wt % to 10 wt %. When the solid content satisfies the above range, since the bundle-type single-walled carbon nanotubes are dispersed at an appropriate level, the carbon nanotube structure can be formed at an appropriate level, and the dispersion stability can be improved. In addition, the electrode slurry can have a viscosity and elasticity suitable for the electrode preparation process, and it also helps to increase the solid content of the electrode slurry.

[0115] In step S1-2, the process of dispersing the bundle-type carbon nanotubes in the mixed solution can be performed by using a mixing device such as a homogenizer, a bead mill, a ball mill, a basket mill, a grinder, a universal stirrer, a transparent mixer, a pin mill, a TK mixer, or an ultrasonic treatment (sonification) device. Among them, the beads mill method is preferred because this method can accurately control the diameter of the carbon nanotube structure, can achieve uniform distribution of the carbon nanotube structure, and can have cost advantages.

[0116] The bead milling method may be as follows: The mixed solution may be put into a container containing beads, and the container may be rotated to disperse the bundle-type single-walled carbon nanotubes.

[0117] In this case, the conditions for performing the bead milling method are as follows.

[0118] The average diameter of the beads may be 0.5 mm to 1.5 mm, for example 0.5 mm to 1.0 mm. When the average diameter satisfies the above range, the diameter of the carbon nanotube structure can be appropriately regulated without destroying the carbon nanotube structure during the dispersion process, and a dispersion solution with a uniform composition can be prepared.

[0119] The rotation speed of the container may be in the range of 500RPM to 10,000RPM, for example, 2,000RPM to 6,000RPM. When the rotation speed satisfies the above range, the diameter of the carbon nanotube structure can be properly regulated without destroying the carbon nanotube structure during the dispersion process, and a dispersion solution with a uniform composition can be prepared.

[0120] The time for performing bead milling can be in the range of 0.5 hours to 2 hours, particularly 0.5 hours to 1.5 hours, and more particularly 0.8 hours to 1 hour. When the time satisfies the above range, the diameter of the carbon nanotube structure can be appropriately regulated without destroying the carbon nanotube structure during the dispersion process, and a dispersed solution with a uniform composition can be prepared. The execution time of bead milling refers to the total time of using bead milling, so, for example, if bead milling is performed several times, the execution time refers to the total time required for performing several bead millings.

[0121] The above bead milling conditions are for dispersing the bundle-type single-walled carbon nanotubes at an appropriate level, and specifically exclude the case where the bundle-type single-walled carbon nanotubes are completely dispersed into single-chain single-walled carbon nanotubes. That is, the above bead milling conditions are for forming a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are combined side by side in a conductive agent dispersion prepared by appropriately dispersing the bundle-type single-walled carbon nanotubes. This can be achieved only when the composition of the mixed solution and the conditions of the dispersion process (e.g., bead milling process) are strictly regulated.

[0122] The carbon nanotube structure dispersion can be formed by the above method.

[0123] (2) Formation of an electrode slurry including a secondary particle dispersion, a carbon nanotube structure dispersion and an electrode active material (S2)

[0124] When the secondary particle dispersion and the carbon nanotube structure dispersion are prepared by the above method, an electrode slurry including the dispersion and the electrode active material is formed. In this case, the above electrode active material can be used as the electrode active material.

[0125] In this case, the electrode active material may be mixed with the carbon nanotube structure dispersion first, and then the secondary particle dispersion may be added. If the mixing is performed in the reverse order, since the carbon nanotube structure cannot be properly dispersed through the π-π bond, the electrode active materials are not connected to each other, and they aggregate with each other, it may not be possible to effectively form a conductive network of the electrode.

[0126] In addition, if necessary, the electrode slurry may further include a binder and a solvent. In this case, the binder of the above embodiment can be used as a binder. The solvent may include, for example: an amide-based polar organic solvent such as dimethylformamide (DMF), diethylformamide, dimethylacetamide (DMAc) and N-methylpyrrolidone (NMP); alcohols such as methanol, ethanol, 1-propanol, 2-propanol (isopropanol), 1-butanol (n-butanol), 2-methyl-1-propanol (isobutanol), 2-butanol (sec-butanol), 1-methyl-2-propanol (tert-butanol), pentanol, hexanol, heptanol or octanol; glycols such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propylene glycol, 1,3-butanediol, 1,5-pentanediol or hexanediol ; Polyhydroxy alcohols such as glycerol, trimethylolpropane, pentaerythritol or sorbitol; Ethylene glycol ethers such as ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, tetraethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, triethylene glycol monoethyl ether, tetraethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether or tetraethylene glycol monobutyl ether; Ketones such as acetone, methyl ethyl ketone, methyl propyl ketone or cyclopentanone; Esters such as ethyl acetate, γ-butyrolactone and ε-propiolactone, and any one of them or a mixture of two or more thereof can be used, but the present invention is not limited thereto. The solvent may be the same as or different from the dispersion medium used in the pre-dispersion, and the solvent may preferably be N-methylpyrrolidone.

[0127] Next, the electrode slurry prepared as described above is dried to form an electrode active material layer. Specifically, the electrode active material layer can be prepared by coating the electrode slurry on an electrode collector and drying the coated electrode collector, or can be prepared by casting the electrode slurry on a separate carrier and then laminating the film separated from the carrier on the electrode collector. If necessary, an electrode active material layer can be formed by the above method, and then a rolling process can be further performed. In this case, taking into account the physical properties of the electrode finally prepared, drying and rolling can be performed under appropriate conditions, and there is no particular restriction.

[0128] Secondary battery

[0129] A secondary battery according to another embodiment of the present invention may include a negative electrode, a positive electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte, and at least one of the positive electrode and the negative electrode may be the electrode of the above embodiment. Specifically, the electrode of the above embodiment may be the positive electrode of this embodiment.

[0130] The separator separates the negative electrode and the positive electrode and provides a mobile path for lithium ions, wherein any separator can be used as a separator without particular limitation, as long as it is generally used for secondary batteries, and in particular, a separator having high moisture retention capacity for electrolytes and low resistance to the transmission of electrolyte ions can be used. Specifically, a porous polymer film can be used, for example, a porous polymer film made of polyolefin-based polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers, or a laminated structure having two or more layers thereof can be used as a separator. In addition, conventional porous nonwoven fabrics can be used, for example, nonwoven fabrics formed by high melting point glass fibers or polyethylene terephthalate fibers. In addition, a coated separator including a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator having a monolayer or multilayer structure can be selectively used.

[0131] The electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, or a molten-type inorganic electrolyte that may be used in the preparation of a lithium secondary battery, but the present invention is not limited thereto.

[0132] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.

[0133] As the non-aqueous organic solvent, for example, aprotic solvents such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran (franc), 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate can be used.

[0134] Especially, in carbonate-based organic solvents, because ethylene carbonate and propylene carbonate as cyclic carbonate dissociate lithium salts well due to high dielectric constant as high viscosity organic solvent, cyclic carbonate can be preferably used.Because when above-mentioned cyclic carbonate is mixed with low viscosity, straight-chain carbonate of low dielectric constant such as dimethyl carbonate and diethyl carbonate and used in appropriate ratio, electrolyte with high conductivity can be prepared, so cyclic carbonate can be more preferably used.

[0135] As the metal salt, a lithium salt may be used, and the lithium salt is a material that is easily soluble in a non-aqueous organic solvent, wherein, as an anion of the lithium salt, for example, at least one selected from the group consisting of: F - , Cl - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - .

[0136] In order to improve the life characteristics of the battery, inhibit the reduction of the battery capacity, and improve the discharge capacity of the battery, in addition to the electrolyte components, at least one additive can be further added to the electrolyte, for example, a halogenated alkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum chloride.

[0137] According to another embodiment of the present invention, a battery module including the secondary battery as a unit cell and a battery pack including the battery module are provided. Since the battery module and the battery pack include secondary batteries having high capacity, high rate performance, and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0138] Hereinafter, the present invention will be described in detail according to specific examples and comparative examples.

[0139] Preparation Example 1: Preparation of Secondary Particle Dispersion

[0140] (1) Formation of primary particles (acetylene black)

[0141] Acetylene black is formed by instantaneously injecting 98% pure acetylene gas into a reactor with an internal temperature of 2000°C, and thermally decomposing the acetylene gas.

[0142] (2) Preparation of secondary particles

[0143] After that, the internal temperature of the reaction furnace containing acetylene black was set to 250°C, and then an oxidation treatment was performed for 30 hours while introducing oxygen. As a result, secondary particles including a chain shape in which a plurality of graphene sheets having a lateral size of about 41 nm were connected to each other were obtained, wherein the secondary particles included a plurality of graphene sheets arranged in different directions. (See Figure 4 (a) and Figure 5 )

[0144] (3) Dispersion preparation

[0145] Secondary particles (powder form), hydrogenated nitrile rubber (H-NBR) as a dispersant and N-methylpyrrolidone (NMP, N-methylpyrrolidone) as a dispersion medium are mixed in a weight ratio of 5.7:1.71:92.59 to form a mixture. This mixture is added to a pin mill in which 80% is filled with beads having a diameter of 0.65 mm, dispersed and discharged at a discharge rate of 2 kg / min. By performing this procedure twice, the secondary particles are fully dispersed to prepare a secondary particle dispersion.

[0146] Preparation Example 2: Preparation of Secondary Particle Dispersion

[0147] The secondary particles used in Preparation Example 1 were subjected to an additional heat treatment at 900° C. for 1 hour in an inert atmosphere, thereby obtaining chain-shaped secondary particles including a plurality of graphene sheets having a lateral size of about 65 nm connected to each other, wherein the secondary particles included a plurality of graphene sheets arranged in different directions. Figure 4 It is understood that, through heat treatment, Figure 4 The secondary particles of Preparation Example 1 shown in (a) are modified to Figure 4 (b) shows the secondary particles of Preparation Example 2. Specifically, it can be understood that the lateral size increases because the adjacent graphene sheets are connected to each other by heat treatment. Thereafter, a dispersion is prepared in the same manner as in the dispersion preparation process of Preparation Example 1 by using the secondary particles.

[0148] Preparation Example 3: Preparation of Carbon Nanotube Structure Dispersion

[0149] Bundle-type single-walled carbon nanotubes (specific surface area 650 m2) consisting of single-walled carbon nanotube units with an average diameter of 1.5 nm and an average length of 5 μm or more 2 / g) and polyvinylidene fluoride (PVdF, KF9700, weight average molecular weight: 880,000 g / mol) were mixed in N-methylpyrrolidone (NMP) as a solvent to prepare a mixture having a solid content of 2.4 wt%.

[0150] The bundle-type single-walled carbon nanotubes were dispersed in the solvent by stirring the mixture by a bead mill method, and thus a carbon nanotube structure dispersion was prepared. In this case, the diameter of the beads was 1 mm, the rotation speed of the stirring container containing the beads was 3,000 RPM, and stirring was performed for 60 minutes. The carbon nanotube structure dispersion includes a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are connected side by side (see Figure 2 A).

[0151] In the carbon nanotube structure dispersion, the amount of the carbon nanotube structure was 0.4 wt %, and the amount of the polyvinylidene fluoride was 2.0 wt %.

[0152] Preparation Example 4: Preparation of Carbon Nanotube Structure Dispersion

[0153] A carbon nanotube structure dispersion was prepared in the same manner as in Preparation Example 3, except that the polyvinylidene fluoride in Preparation Example 3 was replaced with hydrogenated nitrile rubber (weight average molecular weight: 260,000 g / mol).

[0154] Preparation Example 5: Preparation of Carbon Black Dispersion

[0155] The specific surface area is 240m2 / g of carbon black (in the form of secondary particles consisting of primary particles with an average diameter of 25nm) and hydrogenated nitrile rubber (weight average molecular weight: 260,000g / mol) were mixed in N-methylpyrrolidone (NMP) as a solvent to prepare a mixture with a solid content of 16.5wt%.

[0156] By stirring the mixture by a bead mill method, carbon black was dispersed in the solvent, and thus a carbon black dispersion was prepared. In this case, the diameter of the beads was 1 mm, the rotation speed of the stirring container containing the beads was 3,000 RPM, and stirring was performed for 60 minutes.

[0157] In the carbon black dispersion, the amount of carbon black was 15 wt % and the amount of hydrogenated nitrile rubber was 1.5 wt %.

[0158] Preparation Example 6: Preparation of single-walled carbon nanotube unit dispersion

[0159] Bundle-type single-walled carbon nanotubes (specific surface area 650 m2) consisting of single-walled carbon nanotube units with an average diameter of 1.5 nm and an average length of 5 μm or more 2 / g) and hydrogenated nitrile rubber (weight average molecular weight: 260,000 g / mol) were mixed in N-methylpyrrolidone (NMP) as a solvent to prepare a mixture with a solid content of 4.4 wt% (0.4 wt% of bundle-type single-walled carbon nanotubes, 4 wt% of hydrogenated nitrile rubber).

[0160] By stirring the mixture by a bead mill method, the bundle-type single-walled carbon nanotubes were dispersed in the solvent, and thus a conductive agent dispersion was prepared. In this case, the diameter of the beads was 1 mm, the rotation speed of the stirring container containing the beads was 3,000 RPM, and stirring for 60 minutes under the above conditions was set as 1 cycle, and a total of 4 cycles were performed (natural cooling was performed for 60 minutes between each cycle). Thus, a single-walled carbon nanotube unit dispersion was prepared (see Figure 2 B). In the dispersion, since the bundle-type single-walled carbon nanotubes are completely dispersed, the single-walled carbon nanotube units exist only as single chain units, and the above-mentioned carbon nanotube structure is not detected. In addition, in the single-walled carbon nanotube unit dispersion, the amount of the carbon nanotube structure is 0.4% by weight, and the amount of the hydrogenated nitrile rubber is 4.0% by weight.

[0161] Preparation Example 7: Preparation of Multi-walled Carbon Nanotube Unit Dispersion

[0162] The bundle-type multi-walled carbon nanotubes, hydrogenated nitrile rubber (H-NBR) as a dispersant, and N-methylpyrrolidone (NMP) as a dispersion medium were mixed in a weight ratio of 4:0.8:95.2 to form a mixture. The mixture was added to a pin mill in which 80% was filled with beads having a diameter of 0.65 mm, dispersed, and discharged at a discharge rate of 2 kg / min. By performing this process twice, the bundle-type multi-walled carbon nanotubes were completely dispersed to prepare a multi-walled carbon nanotube unit dispersion.

[0163] Preparation Example 8: Preparation of graphene dispersion

[0164] Graphene (in powder form), hydrogenated nitrile rubber (H-NBR) as a dispersant, and N-methylpyrrolidone (NMP) as a dispersion medium were mixed in a weight ratio of 3.6:1.2:95.2 to form a mixture. The mixture was added to a pin mill in which 80% was filled with beads having a diameter of 0.65 mm, dispersed, and discharged at a discharge rate of 2 kg / min. By performing this process twice, the chemically expanded graphene was completely dispersed to prepare a graphene dispersion.

[0165] Examples and Comparative Examples

[0166] Example 1: Preparation of positive electrode

[0167] The secondary particle dispersion of Preparation Example 1, the carbon nanotube structure dispersion of Preparation Example 3, and LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622) and a binder (polyvinylidene fluoride: PVDF, KF9700) were mixed with N-methylpyrrolidone (NMP) to prepare a positive electrode slurry with a solid content of 69.2%. The positive electrode slurry was coated on a 20 μm thick aluminum (Al) film collector, dried at 130 ° C, and then rolled to prepare a positive electrode including a positive electrode active material layer.

[0168] 97.8 wt% LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), 1.71 wt% of polyvinylidene fluoride, 0.09 wt% of hydrogenated nitrile rubber, 0.3 wt% of secondary particles, and 0.1 wt% of carbon nanotube structure were included in the positive electrode active material layer.

[0169] Reference Figure 6 , Figure 7 and Figure 8 It can be confirmed that, in the positive electrode of Example 1, the carbon nanotube structure in the form of a rope forms a network structure to connect the NCM622 particles to each other. In addition, it can be confirmed that the secondary particles tightly form a conductive network while covering the carbon nanotube structure.

[0170] Example 2: Preparation of positive electrode

[0171] A positive electrode was prepared in the same manner as in Example 1, except that the secondary particle dispersion of Preparation Example 2 was used instead of the secondary particle dispersion of Preparation Example 1.

[0172] Example 3: Preparation of positive electrode

[0173] A positive electrode was prepared in the same manner as in Example 1, except that the carbon nanotube structure dispersion of Preparation Example 4 was used instead of the carbon nanotube structure dispersion of Preparation Example 3 in Example 1.

[0174] Example 4: Preparation of positive electrode

[0175] A positive electrode was prepared in the same manner as in Example 1, except that by changing the amounts of the secondary particle dispersion of Preparation Example 1 and the carbon nanotube structure dispersion of Preparation Example 3 used, 0.2 wt % of the secondary particles and 0.1 wt % of the carbon nanotube structure were included in the final positive electrode.

[0176] Comparative Example 1: Preparation of positive electrode

[0177] A positive electrode was prepared in the same manner as in Example 1, except that the carbon black dispersion of Preparation Example 5 was used instead of the secondary particle dispersion of Preparation Example 1 and the carbon nanotube structure dispersion of Preparation Example 3.

[0178] Comparative Example 2: Preparation of positive electrode

[0179] A positive electrode was prepared in the same manner as in Example 1, except that only 0.7 wt % of the secondary particle dispersion of Preparation Example 1 was used instead of the carbon nanotube structure dispersion of Preparation Example 3.

[0180] Comparative Example 3: Preparation of positive electrode

[0181] A positive electrode was prepared in the same manner as in Example 1, except that only 0.7 wt % of the carbon nanotube structure dispersion of Preparation Example 3 was used instead of the secondary particle dispersion of Preparation Example 1.

[0182] Comparative Example 4: Preparation of positive electrode

[0183] A positive electrode was prepared in the same manner as in Example 1, except that the single-walled carbon nanotube unit dispersion of Preparation Example 6 was used instead of the carbon nanotube structure dispersion of Preparation Example 3. Fig. 9 , only short single-walled carbon nanotube units were observed in the positive electrode of Comparative Example 4, and no carbon nanotube structure was observed.

[0184] Comparative Example 5: Preparation of positive electrode

[0185] A positive electrode was prepared in the same manner as in Example 1, except that the multi-walled carbon nanotube unit dispersion of Preparation Example 7 was used instead of the carbon nanotube structure dispersion of Preparation Example 3.

[0186] Comparative Example 6: Preparation of positive electrode

[0187] A positive electrode was prepared in the same manner as in Example 1, except that the graphene dispersion of Preparation Example 8 was used instead of the secondary particle dispersion of Preparation Example 1.

[0188] [Table 1]

[0189]

[0190] In Examples 1, 2 and 4 and Comparative Examples 3 and 6, the average diameter of the carbon nanotube structure was 100 nm, and the average length thereof was 15.6 μm. In Example 3, the average diameter of the carbon nanotube structure was 10 nm, and the average length thereof was 8.2 μm. In Comparative Example 4, the average diameter of the single-walled carbon nanotube unit was 1.6 nm, and the average length thereof was 1.8 μm.

[0191] In Comparative Example 5, the average diameter of the multi-walled carbon nanotube units was 10.8 nm, and the average length thereof was 1.3 μm.

[0192] When the prepared positive electrode is observed by TEM, the average diameter and the average length correspond to the average value of the diameters (or lengths) of the first 100 carbon nanotube structures (or multi-walled carbon nanotube units, or single-walled carbon nanotube units) with larger diameters (or lengths) and the last 100 carbon nanotube structures (or multi-walled carbon nanotube units, or single-walled carbon nanotube units) with smaller diameters (or lengths).

[0193] In Comparative Example 6, the average length of the graphene is 4.6 μm and the average thickness thereof is 5.3 nm, and when the prepared positive electrode is observed by TEM, the average length and the average thickness correspond to the average value of the length (or thickness) of the first 100 graphenes with larger lengths (or thicknesses) and the length (or thickness) of the last 100 graphenes with smaller lengths (or thicknesses).

[0194] The physical properties of the secondary particles included in the positive electrodes of Examples 1, 3 and 4 and Comparative Examples 2, 4 and 5 (secondary particles of Preparation Example 1), and the secondary particles included in the positive electrode of Example 2 (secondary particles of Preparation Example 2) are as follows.

[0195] [Table 2]

[0196]

[0197] 1) Lateral size (nm) of graphene sheets included in the secondary particles: The sizes of 100 graphene sheets included in the secondary particles in the positive electrode were measured using TEM (JEOL, JEM-2010F), and the average value of these sizes was used for evaluation. 2) Nitrogen adsorption specific surface area (m 2 / g): measured by degassing at 200°C for 8 hours and performing N2 adsorption / desorption at 77 K using a BET meter (BEL-SORP-MAX, Nippon Bell). 3) Iodine adsorption value (mg / g): measured according to ASTM D1510.

[0198] 4) Oxygen content (wt%): The contents of C, H and N elements were measured by an element analyzer (CHN encoder MT-5, Yanako), and the oxygen content (differential) was calculated to reflect the amount of residual ash.

[0199] 5) Raman spectroscopy D / G ratio: measured by analyzing a Raman spectrum obtained using an Ar ion laser having a wavelength of 514.5 nm by a Raman spectrometer (NRS-2000B, Jasco).

[0200] Reference Figure 6 , 7 and 8. For all the positive electrodes of the embodiments of the present invention, it can be understood that the carbon nanotube structure in the form of a flexible long rope (in which 2 to 5,000 single-walled carbon nanotube units are arranged side by side and bonded to each other) and the secondary particles form a good conductive network structure in the positive electrode active material layer.

[0201] Test Example 1: Evaluation of Powder Resistance of Electrode Slurry

[0202] The powder resistance of the electrode slurry formed in the preparation of the positive electrodes of Examples 1 to 4 and Comparative Examples 1 to 6 was evaluated by the following method.

[0203] The positive electrode slurry was vacuum dried at a temperature of 130° C. for 3 hours and then ground to prepare a powder. Thereafter, the powder was prepared into pellets using a Loresta GP instrument purchased from Mitsubishi Chem Analytic Co., Ltd. at 25° C. under a load of 9.8 MPa and a relative humidity of 50%. Thereafter, the powder resistance was measured by a 4-probe method, and the results are shown in Table 3.

[0204] Test Example 2: Battery Life Characteristics Evaluation

[0205] Batteries were prepared using the positive electrodes of Examples 1 to 4 and Comparative Examples 1 to 6 as follows.

[0206] Artificial graphite as a negative electrode active material, carbon black as a negative electrode conductive agent, styrene butadiene rubber (SBR) as a negative electrode binder, and carboxymethyl cellulose (CMC) were mixed in distilled water at a weight ratio of 96.1:0.5:2.3:1.1 to prepare a negative electrode slurry. A 20 μm thick negative electrode collector (Cu) was coated with the prepared slurry so that the loading amount was 10 mg / cm 2 , and dried. Thereafter, the negative electrode current collector on which the negative electrode slurry was arranged was rolled by a rolling method so that the total thickness of the negative electrode slurry and the negative electrode current collector was 80 μm. Thereafter, the negative electrode slurry and the negative electrode current collector were dried at 110° C. for 6 hours to prepare a negative electrode.

[0207] Afterwards, after preparing a single cell by assembling the above-prepared negative electrode and the above-prepared positive electrode with a 15μm thick polyethylene-based separator arranged therebetween, an electrolyte (ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 1 / 2 (volume ratio)) and lithium hexafluorophosphate (1M LiPF6) are injected into the single cell to prepare a lithium secondary battery.

[0208] Charging and discharging of each lithium secondary battery was performed under the following conditions.

[0209] Each lithium secondary battery was set to charge / discharge at 0.33C / 0.33C in a voltage range of 4.25V to 2.8V at 45°C for one cycle, and a total of 100 cycles were performed. Thereafter, the discharge capacity (capacity retention rate) after 100 cycles was evaluated based on the discharge capacity after 1 cycle being 100%, and is shown in Table 3.

[0210] [Table 3]

[0211] Powder resistance of positive electrode slurry (Ω) Capacity retention rate (%) Example 1 15.7 96.1 Example 2 14.9 96.8 Example 3 18.1 95.3 Example 4 17.6 95.1 Comparative Example 1 253.3 79.4 Comparative Example 2 53.7 90.8 Comparative Example 3 15.1 93.6 Comparative Example 4 98.9 85.3 Comparative Example 5 75.6 88.2 Comparative Example 6 218.7 80.3

[0212] The following content corresponds to the original claims in the parent application and is now incorporated herein as part of the specification:

[0213] 1. An electrode comprising an electrode active material layer,

[0214] The electrode active material layer comprises an electrode active material and a conductive agent,

[0215] The conductive agent includes a first conductive agent and a second conductive agent,

[0216] wherein the first conductive agent comprises a secondary particle in which a portion of one graphene sheet is connected to a portion of another adjacent graphene sheet, and the secondary particle comprises a plurality of graphene sheets arranged in different directions,

[0217] The second conductive agent includes a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded to each other, and

[0218] The carbon nanotube structure is included in the electrode active material layer in an amount of 0.01 wt % to 0.5 wt %.

[0219] 2. An electrode according to item 1, wherein a weight ratio of the secondary particles to the carbon nanotube structure is in the range of 100:1 to 100:200.

[0220] 3. The electrode according to item 1, wherein the secondary particles are included in the electrode active material layer in an amount of 0.01 wt % to 1.0 wt %.

[0221] 4. The electrode according to item 1, wherein the carbon nanotube structures are interconnected in the electrode to form a network structure.

[0222] 5. The electrode according to item 1, wherein the single-walled carbon nanotube units are arranged and combined side by side in the carbon nanotube structure.

[0223] 6. The electrode according to item 1, wherein the average length of the carbon nanotube structure is 1 μm to 500 μm.

[0224] 7. The electrode according to item 1, wherein the average length of the carbon nanotube structure is 10 μm to 70 μm.

[0225] 8. The electrode according to item 1, wherein the average diameter of the carbon nanotube structure is 2 nm to 200 nm.

[0226] 9. The electrode according to item 1, wherein the average diameter of the carbon nanotube structure is 50 nm to 120 nm.

[0227] 10. The electrode according to item 1, wherein the average diameter of the single-walled carbon nanotube units is 0.5 nm to 5 nm.

[0228] 11. An electrode according to item 1, wherein the oxygen content of the secondary particles is in the range of 1 wt% to 10 wt% based on the total weight of the secondary particles.

[0229] 12. The electrode according to item 1, wherein the carbon nanotube structure is a carbon nanotube structure in which 50 to 4,000 single-walled carbon nanotube units are bonded to each other.

[0230] 13. An electrode according to item 1, wherein the lateral dimension of the graphene sheet is 10 nm to 500 nm.

[0231] 14. An electrode according to item 1, wherein during Raman spectroscopy measurement, the D / G peak ratio of the secondary particles is 0.9 to 2.0.

[0232] 15. An electrode according to item 1, wherein the secondary particles have a value of 0 to 0.2 calculated by equation 1:

[0233] [Equation 1]

[0234]

[0235] Wherein, in Equation 1, a is the specific surface area (m 2 / g), b is the iodine adsorption value of the secondary particles (mg / g).

[0236] 16. The electrode according to item 1, wherein the secondary particle further comprises a connecting portion connected to at least a portion of the graphene sheets in the plurality of graphene sheets,

[0237] Wherein, the connecting portion has a non-graphene shape.

[0238] 17. An electrode according to item 16, wherein at least a portion of each of the plurality of graphene sheets is connected to the connecting portion.

[0239] 18. An electrode according to item 1, wherein the average thickness of the graphene sheet is 0.34 nm to 10 nm.

[0240] 19. An electrode according to claim 1, wherein the specific surface area (m 2 / g) is 200m 2 / g to 1100m 2 / g.

[0241] 20. An electrode according to claim 1, wherein the electrode is a positive electrode.

[0242] 21. A secondary battery comprising the electrode according to any one of items 1 to 20.

Claims

1. An electrode comprising an electrode active material layer, The electrode active material layer comprises an electrode active material and a conductive agent, The conductive agent includes a first conductive agent and a second conductive agent, wherein the first conductive agent includes secondary particles in the form of chains in which a plurality of graphene sheets are arranged in different directions and a portion of one graphene sheet is connected to a portion of another adjacent graphene sheet, The second conductive agent includes a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded to each other. 2 . The electrode according to claim 1 , wherein a weight ratio of the secondary particles to the carbon nanotube structure is in a range of 100:1 to 100:

200. 3 . The electrode according to claim 1 , wherein the secondary particles are included in the electrode active material layer in an amount of 0.01 wt % to 1.0 wt %. The electrode according to claim 1 , wherein the carbon nanotube structures are interconnected in the electrode to form a network structure. 5 . The electrode according to claim 1 , wherein the single-walled carbon nanotube units are arranged and combined side by side in the carbon nanotube structure. The electrode according to claim 1 , wherein the carbon nanotube structure has an average length of 1 μm to 500 μm. 7 . The electrode according to claim 1 , wherein an average length of the carbon nanotube structure is 10 μm to 70 μm. The electrode according to claim 1 , wherein the carbon nanotube structure has an average diameter of 2 nm to 200 nm. 9 . The electrode according to claim 1 , wherein the average diameter of the carbon nanotube structure is 50 nm to 120 nm. 10 . The electrode according to claim 1 , wherein the single-walled carbon nanotube unit has an average diameter of 0.5 nm to 5 nm.

11. The electrode according to claim 1, wherein The oxygen content of the secondary particles is in the range of 1 wt % to 10 wt % based on the total weight of the secondary particles. 12 . The electrode according to claim 1 , wherein the carbon nanotube structure is a carbon nanotube structure in which 50 to 4,000 single-walled carbon nanotube units are bonded to each other.

13. The electrode according to claim 1, wherein the lateral dimension of the graphene sheet is 10 nm to 500 nm. 14 . The electrode according to claim 1 , wherein a D / G peak ratio of the secondary particles is 0.9 to 2.0 during Raman spectroscopy measurement.

15. The electrode according to claim 1, wherein the secondary particles have a value of 0 to 0.2 calculated by Equation 1: [Equation 1] in, In Equation 1, a is the specific surface area (m 2 / g), b is the iodine adsorption value of the secondary particles (mg / g).

16. The electrode according to claim 1, wherein the secondary particle further comprises a connecting portion connected to at least a portion of the graphene sheets among the plurality of graphene sheets, in, The connecting portion has a non-graphene shape. 17 . The electrode according to claim 16 , wherein at least a portion of each of the plurality of graphene sheets is connected to the connection portion.

18. The electrode according to claim 1, wherein the average thickness of the graphene sheet is 0.34 nm to 10 nm.

19. The electrode according to claim 1, wherein the specific surface area (m 2 / g) is 200m 2 / g to 1100m 2 / g.

20. The electrode of claim 1, wherein the electrode is a positive electrode.

21. A secondary battery comprising the electrode according to any one of claims 1 to 20.

Citation Information

Patent Citations

  • System and method for lending clothes in online

    KR1020190122964A